EDUKASI PENGELOLAAN BEBAN KERJA UNTUK OPTIMALISASI KEPUASAN PEKERJA PADA MASYARAKAT DESA WAWORAHA, KECAMATAN SOROPIA, KABUPATEN KONAWE - Zainuddin, Asnia; Saptaputra, Syawal Kamiluddin (Universitas Halu Oleo, 2024)
Workload is a difference between the capacity or ability of workers and the job demands that must be faced. Inappropriate workload has an impact on employee job satisfaction which results in low employee performance. The results of observations made during field observations found several complex problems, such as the relationship between leaders and subordinates which was less than harmonious, such as communication from superiors to subordinates which was not smooth and cooperation which existed less than optimally so that subordinates felt uncomfortable in carrying out their work, so it became worthy of research. . Therefore, creating work programs related to increasing knowledge on how to manage excessive workload through educating the public is very important to increase worker satisfaction. The aim of this service is to increase the knowledge of the Waworaha Village community about how to manage excessive workload. The method used in service is an offline educational method. The result of this service is that workers can understand and implement efforts to deal with excessive workloads in order to increase worker satisfaction.